1964
DOI: 10.1055/s-0038-1655573
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenic Properties of Surface Factor; Evidence for an Anti-Surface Factor Activity in Canine Plasma.

Abstract: SummaryPurified surface factor (SF or activation product) was prepared from canine plasma and its effect was studied on 22 dogs. It was shown that intravenous injection of SF increased the coagulability of the circulating blood (in vitro tests) and induced thrombosis in areas of vascular stasis (in vivo assay). The hypercoagulability was associated with the injected SF preparation and with no other known clotting factor increase. A second injection performed 61 minutes after the first was less effective. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1966
1966
1974
1974

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Thus it is possible that, in the present experiments, HF was unable to be activated on the surface of the aspirinized platelets since these platelets remained intact and consequently no hypercoagulation observed. In the non-aspirinized animals, however, AlPh aggregated the platelets upon the altering surfaces of which HF is probably activated to induce t he hypercoagulation noted in the present experiments as well as in previous studies (10,12).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus it is possible that, in the present experiments, HF was unable to be activated on the surface of the aspirinized platelets since these platelets remained intact and consequently no hypercoagulation observed. In the non-aspirinized animals, however, AlPh aggregated the platelets upon the altering surfaces of which HF is probably activated to induce t he hypercoagulation noted in the present experiments as well as in previous studies (10,12).…”
Section: Discussionsupporting
confidence: 77%
“…Since aspirin has no direct effect on any of the known clotting factors (14,16) it is possible that the hypercoagulation observed in the non-aspirinized animals was due to the increased platelet aggregation and adhesion after ALPh injection. It has been shown previously (12) that SF (XIa + XIIa) is one of the main clotting factors for inducing hypercoagulation. Also it has been shown (8,9) that Hageman factor (HF or factor XII) could be activated on the surface of the altering platelets and consequently could trigger the clotting mechanism and induce a hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
“…In the extensive studies of Wessler and his co-workers it has been shown that their serum thrombotic accelerator, STA, defined responsible for the initiation of thrombosis in isolated venous segments, is more or less dependent on HF, AHC and AHB and on surface activation of the injected serum fractions ( 41,42). The thrombosis-inducing property of a concentrate of AHC' in stasis conditions in experimental animals was later also confirmed by others (11,16,17). These results are in good accordance with the experiments of Connor et al (5,14) producing thrombosis in dogs by infusions of long-chain saturated fatty acids which were known to activate HF.…”
Section: Discussionmentioning
confidence: 84%
“…III, IV, V) to suggest that the "beta" fraction contains the factor responsible for the stated acceleratory effect of alkaline phosphatase on clotting. In previous studies, as well as others [cited (14)], a key role of SF is emphasized in the induction of a hypercoagulable state which, in the presence of other contributory factors (such as local stasis of the circulation), strongly favors the incidence of thrombosis. Thomas et al ( 27) also emphasize the importance of factor IX in hypercoagula ble states.…”
Section: Discussionmentioning
confidence: 90%
“…The important protective role of the plasmatic inhibitor of SF (anti-SF) is emphasized by Iatridis et al (14,17). In a recent study (10) evidence was presented that ATP-ase (Apyrase form) is a specific in vitro inhibitor of active SF.…”
Section: Discussionmentioning
confidence: 99%